Direct Utilization of Geothermal Energy in Menengai, Kenya: Pilot Project for Drying Food Commodities in Lesiolo, Nakuru - Allen Haryanto Lukmana Lukmana (Journal of Petroleum and Geothermal Technology, 2020)
Kenya is a developing country highly dependent on economic rotation in agricultural sector with main commodities corn, tea and fruits. In order to maintain quality of commodity within a certain period, a drying process is needed. Purpose of drying is to reduce moisture content of a commodity to a certain level. Alternative energy that can be used for drying activities in Kenya is geothermal energy. In assessing direct utilization of geothermal energy, a pilot project was made in Lesiolo, Nakuru by utilizing heat energy from the Menengai geothermal waste fluid area, Nakuru. Drying process can utilize brine from separator or condensate from power plant by using a heat exchanger to get required drying temperature. One drying room can hold about 20 tons in ambient air conditions. This dryer is shaped like a tunnel where hot air will flow from each side of drying chamber. Food commodities used in this project are wheat, corn and barley. Heat energy needed to dry each of these food commodities comes from geothermal waste fluid that enters heat exchanger with a minimum input temperature of 130oC and an output of 93oC. Mass flow rate needed to dry every 30 m3 of commodity is 2 kg/s